1968
DOI: 10.1037/h0025873
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy, autonomic functioning, and the orienting response.

Abstract: Autonomic activity was continuously recorded while primary psychopaths (P), secondary psychopaths (S), and nonpsychopaths (NP) listened to a series of repetitive tones and solved simple arithmetic problems. During rest, Group P had lower levels of skin conductance and autonomic variability than did Group NP, but the difference in autonomic variability disappeared during the arithmetic period. Group P was generally less autonomically responsive to the tones, particularly when GSR and cardiac responses were expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 79 publications
6
42
1
1
Order By: Relevance
“…This collection of abnormalities suggests that psychopaths have difficulty in fear conditioning, are relatively lacking in fear, and do not respond well in classical conditioning paradigms with punishment contingencies. An alternative interpretation, first proposed by Hare (1968), is that these results suggest abnormalities in orienting processes. That is, in all the psychophysiological studies listed above, an orienting response would be elicited by the salient cues or stimuli.…”
Section: Attention and Orienting Processes In Psychopathsmentioning
confidence: 97%
“…This collection of abnormalities suggests that psychopaths have difficulty in fear conditioning, are relatively lacking in fear, and do not respond well in classical conditioning paradigms with punishment contingencies. An alternative interpretation, first proposed by Hare (1968), is that these results suggest abnormalities in orienting processes. That is, in all the psychophysiological studies listed above, an orienting response would be elicited by the salient cues or stimuli.…”
Section: Attention and Orienting Processes In Psychopathsmentioning
confidence: 97%
“…Some of the first physiological evidence for these models demonstrated that psychopaths fail to show appropriate autonomic responses in conditioning paradigms (Hare and Quinn 1971; Lykken 1957), and in anticipation of aversive stimuli (Hare 1968, 1982; Hare et al 1978). This trend has been replicated in many different contexts, as psychopaths show relatively subdued physiological responses to emotionally evocative stimuli including sounds (Verona et al 2004), emotional words (Williamson et al 1991), and disturbing images (Herpertz et al 2001).…”
Section: Neurobiological Models Of Psychopathymentioning
confidence: 99%
“…Maddi (231) and Jacobovits (171) have both critically evaluated the evi dence for both the accuracy and the generality of such an effect of "mere exposure" over wider ranges of exposure frequency and an array of different stimulus objects. Hare (152) plotted habituation to novel stimuli observed in autonomic recordings from groups of psychopathic and nonpsychopathic prisoners. Although he found differences between these groups in initial reactivity for the stimuli that he employed, they followed similar habituation curves over successive exposures.…”
Section: The Study Of Personality Systemsmentioning
confidence: 99%